Enhancing English Vocabulary Acquisition of Indonesian EFL Students through Auditory Feedback in Quizizz - Tamam, Avila Akhtar; Kasim, Ahmad (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This quasi-experimental study investigates the efficacy of auditory feedback in Quizizz, a gamified learning platform, for enhancing vocabulary acquisition among Indonesian EFL learners. Sixty-two 11th-grade students from SMA 1 Tenggarong were assigned to an experimental group (n=34) using Quizizz with auditory feedback and a control group (n=28) receiving traditional teacher-led instruction. Over four 60-minute sessions across two weeks, both groups studied identical vocabulary content. Pre- and post-tests employing the Vocabulary Size Test (Nation & Beglar, 2007) measured receptive vocabulary gains, while a bilingual Intrinsic Motivation Inventory (Ryan & Deci, 2000) assessed perceptions. Results revealed significantly greater vocabulary improvement in the experimental group (mean gain +0.20 vs. control's -0.28; *t*(60)=2.34, *p*=.023, *d*=0.42), with notably higher motivation scores across all subscales (Interest, Competence, Effort, Value; *p*<.05). These findings align with Mayer's (2009) Cognitive Theory of Multimedia Learning, demonstrating that auditory-enhanced digital instruction outperforms conventional methods in both cognitive and affective domains. The study advocates for integrating multimodal feedback in EFL pedagogy, particularly in contexts seeking to optimize limited instructional time